Armenian cochineal (Porphyrophora hamelii) and purpurin‐rich madder in ancient polychromy. (11th September 2015) - Mantzouris, Dimitrios; Karapanagiotis, Ioannis
<x xml:space="preserve">Abstract</x> Samples removed from funeral figurines, dated the third to the second century BC (Hellenistic period) and found in Macedonia, Greece, are investigated using high‐performance liquid chromatography. Two results are reported that provide new insights into ancient polychromy. Firstly, high‐performance liquid chromatography results, in combination with historical information, indicate that insect species of cochineal, most probably Porphyrophora hamelii Brandt, was used in Hellenistic objects. Secondly, madder detected in the archaeological samples contains high amounts of purpurin (alizarin is either not detected or detected in trace). This relative composition, which is recorded using the hydrochloric acid method for dyestuff extraction, is consistent with that prepared from wild madder (Rubia peregrina L.), which is a common plant in the Mediterranean region.